2020
DOI: 10.3390/biom10091276
|View full text |Cite
|
Sign up to set email alerts
|

The Role of HDL and HDL Mimetic Peptides as Potential Therapeutics for Alzheimer’s Disease

Abstract: The role of high-density lipoproteins (HDL) in the cardiovascular system has been extensively studied and the cardioprotective effects of HDL are well established. As HDL particles are formed both in the systemic circulation and in the central nervous system, the role of HDL and its associated apolipoproteins in the brain has attracted much research interest in recent years. Alzheimer’s disease (AD) is the most prevalent neurodegenerative disorder and the leading cause of dementia worldwide, for which there cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 236 publications
(309 reference statements)
0
14
0
Order By: Relevance
“…Potentially, HDL exerts its neuroprotective effects through the redistribution of lipids which may affect neuronal membrane composition. This may have reverberating effects on β deposition and p-tau accumulation, and may protect neurons against oxidation and inflammation, thereby preserving vascular and synaptic function [40,42,43]. Total lipids, cholesteryl esters, cholesterol, triglycerides in VLDL and LDL subclasses, and polyunsaturated fatty acids (PUFA) were inversely associated with future risk of dementia, while free cholesterol concentration in very large VLDL was associated with an increased risk of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, HDL exerts its neuroprotective effects through the redistribution of lipids which may affect neuronal membrane composition. This may have reverberating effects on β deposition and p-tau accumulation, and may protect neurons against oxidation and inflammation, thereby preserving vascular and synaptic function [40,42,43]. Total lipids, cholesteryl esters, cholesterol, triglycerides in VLDL and LDL subclasses, and polyunsaturated fatty acids (PUFA) were inversely associated with future risk of dementia, while free cholesterol concentration in very large VLDL was associated with an increased risk of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the role of apoE in Alzheimer’s disease development and other neurologic diseases, apoE mimetic peptides have also been tested in various neurologic disease animal models and have yielded promising results [ 111 ]. One example of an apoE mimetic peptide designed for Alzheimer’s disease is CN-105 (Cerenova, LLC) ( Table 4 ).…”
Section: Apoementioning
confidence: 99%
“…It was tested in 48 subjects in a phase 1 trial and shown to be safe [ 104 ]. Several other apoE-based peptides for neurologic diseases are actively being developed and have recently been reviewed [ 111 ].…”
Section: Apoementioning
confidence: 99%
“…apoA-I-rHDL containing elaidic acid showed impaired HDL functionality via the displacement of apoA-I from the rHDL [ 32 ]. Several atherogenic changes in HDL by carbohydrate and trans fat HDL show that good-quality HDL reduces the risk of AD via the natural clearance of Aβ [ 34 ].…”
Section: Discussionmentioning
confidence: 99%